2009
DOI: 10.1161/circulationaha.109.851881
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-2 Mediates Inflammation and Matrix Degradation in Human Atherosclerosis

Abstract: Background— Inflammation and matrix degradation are the hallmarks of high-risk atherosclerosis that leads to myocardial infarction and stroke. Toll-like receptors (TLRs), key players in innate immunity, are upregulated in atherosclerotic lesions, but their functional role in human atherosclerosis is unknown. We explored the effects of blocking TLR-2, TLR-4, and myeloid differentiation primary response gene 88 (MyD88), a signaling adaptor shared by most TLRs and interleukin-1 receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
2
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 49 publications
6
120
2
11
Order By: Relevance
“…12,13 Moreover, unlike TLR4 blockade, neutralizing TLR2 can inhibit the expression of NF-iB and the release of interleukin-6 (IL-6), IL-8, and matrix metalloproteinases. 14 Compared to TLR4, up-regulation of TLR2 had much more significant influence on plaque varying from vulnerability to rupture, 14 which was consistent with study by Mullick's et al, 15 that higher expression of TLR2 was detected in artery lesion-prone area of mouse. TLR2 modulates inflammatory cascade.…”
Section: Introductionsupporting
confidence: 77%
“…12,13 Moreover, unlike TLR4 blockade, neutralizing TLR2 can inhibit the expression of NF-iB and the release of interleukin-6 (IL-6), IL-8, and matrix metalloproteinases. 14 Compared to TLR4, up-regulation of TLR2 had much more significant influence on plaque varying from vulnerability to rupture, 14 which was consistent with study by Mullick's et al, 15 that higher expression of TLR2 was detected in artery lesion-prone area of mouse. TLR2 modulates inflammatory cascade.…”
Section: Introductionsupporting
confidence: 77%
“…Native LDL and electronegative LDL increase the expression and release of interleukin (IL)-8, monocyte chemoattractant protein-1, and IL-6 in human umbilical artery endothelial cells (6). TLR2 and TLR4 play important roles in the vascular inflammatory response and are involved in the initiation and progression of atherosclerosis (7)(8)(9)(10). Increased endothelial expression of TLR2 at sites of disturbed blood flow exacerbates early atherogenic events (11).…”
mentioning
confidence: 99%
“…Consequently, there is an important need to identify if other elements play a key role in the progression and embolism from carotid plaques. Nowadays, the importance of inflammation and inflammatory markers has been claimed as a fundamental factor involved in the development and progression of the atherosclerotic plaques; furthermore, the association between inflammation, atherosclerosis progression and cardiovascular events have been well established for coronary and carotid artery diseases (Libby, 2002;Ridker, 2003, Monaco 2009, Monaco 2010, Shalhoub 2009. Histological studies have observed that stable plaques are indeed characterized by a chronic inflammatory infiltrate, whereas vulnerable and ruptured plaques are characterized by an active inflammation and "plaque activity" processes involved in the thinning of the fibrous cap, predisposing to plaque rupture (de Nooijer, 1996;Spagnoli, 2004;Spagnoli, 2007).…”
Section: Role Of Inflammation and Intraplaque Angiogenesismentioning
confidence: 99%